Baseline Stroke Literacy of Young Children Based on “FAST 112 Heroes” Program - Tsakpounidou, Kalliopi; Psomiadis, Socrates; Pourliaka, Tatiana; Akritidou, Maria; Proios, Hariklia (Frontiers in Public Health, 2021)
Background: Young children are often unaware of emergency health conditions, such as stroke, and could serve as important vehicles to save the lives of their grandparents, who are more likely to suffer a stroke. An important aspect for the evaluation of public awareness on stroke signs and related emergency procedures is to examine the level of baseline stroke knowledge children have and whether they understand when to seek medical care on time. Objective: To examine the level of stroke symptomatology knowledge in children as well as evaluate their preparedness in stroke response before their participation in the educational programme “FAST (Face, Arms, Speech, Time) 112 Heroes”. Methods: For the purpose of this work, a questionnaire was developed and adapted to preschoolers’ needs. The present study involved 123 children (65 boys, 58 girls, aged 4-6.5 years; mean age: 5.30, S.D.: 0.59) from two cities in Greece. Five multiple- choice animated pictures, that were age-appropriate, were administrated to each child, along with verbal explanations provided by the investigator. Results: More than half of the participants (n=65, 52.8%) could recognize the symptom of face drooping, 53 children (43.1%) could identify the symptom of arm hemiparesis/hemiplegia and 92 children (74.8%) were able to answer the question regarding speech disturbances. However, the number of correct answers to the question regarding the appropriate course of action in case of a stroke was the lowest among all the questions (10.6% of participants gave a correct answer). Furthermore gender and age did not play a significant role (p=0.571 and p=0.635, respectively). Conclusion: Although more than half of the enrolled preschool children could recognize stroke symptoms before their participation in the educational programme, their baseline stroke knowledge, prior to their training, is low. Concurrently, they do not have sufficient knowledge on how to react appropriately in the event of a stroke. Therefore, awareness programmes focusing on developing stroke literacy to children are needed, to ensure children will seek urgent medical care in case of a stroke.